2023
DOI: 10.3389/fpsyg.2023.1107935
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in behavioral inhibitory control under evoked acute stress: An event-related potential study

Abstract: PurposeThis study investigated gender differences in behavioral inhibitory control among college students under acute stress state by using event-related potential technique.MethodsAcute stress was evoked in 41 college students (22 males and 19 females) using the Trier Social Stress paradigm, and the neutral state was matched using out-of-speech reading, with subjects completing a two-choice Oddball task in each of the two states. In combination with the ERP technique, the area under the stress curve, reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
1
0
0
Order By: Relevance
“…In the measurement of behavioral inhibit control functioning, we found that both ADHD and TDC had lower accuracy and longer response time on deviant stimuli than on standard stimuli, which was consistent with the results of previous studies on substance addiction [30] and normal population [54].…”
Section: Discussionsupporting
confidence: 91%
“…In the measurement of behavioral inhibit control functioning, we found that both ADHD and TDC had lower accuracy and longer response time on deviant stimuli than on standard stimuli, which was consistent with the results of previous studies on substance addiction [30] and normal population [54].…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, another study found that there were sex differences in selective attention [61]. In addition, it was found that there were sex differences in inhibitory control among university students [62]. Complementary to the above, another study reported sex differences in EFs in university students [63].…”
Section: Discussionmentioning
confidence: 74%
“…3,4 Interestingly, severe acute stress is a critical risk factor for psychiatric disease development disproportionately in females, intimating that there may be sex differences in how acute stress is encoded at synapses relevant to psychiatric disease pathogenesis. [5][6][7][8] However, the cellular mechanisms by which acute stress induces vulnerability to psychiatric disease remain obscure, and even less is understood regarding how acute stress impacts vHipp synapses while considering sex as a biological variable.…”
Section: Introductionmentioning
confidence: 99%